Who is affected by parental leave reforms? Women's selection into different parental leave lengths across recent policy reforms in Germany - Lara Bister; Peter Eibich; Roberta Rutigliano (Genus, 2024)
Public parental leave schemes aim to facilitate women's reconciliation of family and employment after their transition into motherhood. While parental leave policies underwent several reforms over the past decades, adapting to changing female labour market participation and family cultures, the available entitlements are not tailored to women's individual circumstances and needs. It remains unclear how these affect the women's parental leave uptake, particularly the leave length. In this paper, we followed an exploratory and descriptive approach to study the selection of women into different parental leave lengths with changing public parental leave entitlements in Germany and according to their individual characteristics. We use data from the German Statutory Pension Fund on 29,001 women born between 1955 and 1984 who had their first child between 1991 and 2016 at the ages 20–39. We estimate linear regression and discrete-time proportional hazard models to examine associations between women's characteristics and their length of leave. We identify the effects of two major parental leave reforms in Germany in 1992 and 2007 in a Regression Discontinuity Design. Our results show that the general extension of available parental leave entitlements in 1992 increased the likelihood of women's parental leave uptake between 25 and 36~months. For women who became mothers at an older age, had a high income before transitioning into motherhood, or with higher education; however, the likelihood of parental leave uptake of 2~months increased. The reform of 2007 led to an increased likelihood of leave uptake longer than 2~months for these women. These findings suggest that women with a higher labour market attachment have responded more strongly to the changes in parental leave benefits in Germany.
Keywords: 320